An Exploration to the Factors Affecting China’s Mergers and Acquisitions Costs - Chen, Ting; Pan, Xia (Archives of Business Research, 2019)
This article is an exploratory study. We explore and discuss the influencing factors that affect the merger and acquisition (M&A). We analysis and comment the valuation in the M&A process, and whether it is worth to do the M&A. We first introduce the topic and research motivation and methods. Then we introduce the process and realization of M&A, and how to evaluate the M&A. Further, we talk about the influence factors in M&A, not only in the financial way, but in a broader market ken. In the last, we make suggestions on how to reduce the risk for a successful M&A.